Defining Seaward Boundaries in a Domestic Context: Norway and the Svalbard Archipelago. (3rd July 2019) - Jensen, Øystein
Abstract: This article analyzes a little-noticed aspect of the international legal controversy pertaining to Svalbard's maritime zones. It concerns where and by which method Norway should draw the boundaries between Svalbard's continental shelf and the 200-mile zone, on the one hand, and other maritime zones subject to Norwegian jurisdiction, on the other. The assumption upon which the discussion rests is that the Spitsbergen Treaty signatories enjoy treaty rights in the maritime zones beyond Svalbard's territorial waters. The law of the sea does not contain rules on the drawing of maritime boundaries between different parts of a state's territory, but the rules on delimitation between states offer a strong analogy. In the search for an equitable solution, primacy should be given to geographical factors. The article argues that Norway could do more to enhance the openness regarding the Svalbard delimitation question since its outcome will be of significant interest to other states.